Assessment of Competence of Pre-service Mathematics and Science Teachers in Classifying Cognitive Processes and Knowledge Dimensions through the Revised Bloom's Taxonomy - Qadar, Riskan; Efwinda, Shelly; Syam, Muliati; Haerani, Rosita Putri Rahmi; Dinurrohmah, Syayidah; Aryaputra, Akmal Raiky; Farida, Saphira Devina Widya Putri (International Journal of STEM Education for Sustainability, 2025)
Effective assessment plays a critical role in fostering students' cognitive development and academic achievement. To achieve this, pre-service mathematics and science teachers must demonstrate competencies in classifying cognitive processes and knowledge dimensions through the Revised Bloom’s Taxonomy (RBT). This study investigated the competencies of 156 pre-service teachers from mathematics, biology, physics, and chemistry education programs at a public university in Indonesia in classifying test items according to RBT. Employing a quantitative descriptive design, participants were evaluated on their ability to accurately identify both cognitive levels (C1–C6) and knowledge dimensions (factual, conceptual, procedural, and metacognitive). The results revealed strong proficiency in analyzing (C4), but notable weaknesses in applying (C3) and creating (C6)—two domains essential for developing higher-order thinking skills (HOTS). Moreover, no statistically significant differences were found between male and female participants. These findings underscore the need for strengthening teacher education curricula by integrating targeted training on RBT-based assessment design. Equipping pre-service teachers with such competencies is vital for enhancing students’ critical thinking and problem-solving abilities.